The Functional Literacy Competence: How to Develop and Measure It for Junior High School Students - Sari, Esti Swatika; Wiyatmi, Wiyatmi; Lestyarini, Beniati (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2025)
Abstract. This study aims to develop and empirically validate a functional literacy competency measurement tool specifically for junior high school students. This instrument can be used by educators and stakeholders to explore and in advanced improve student’s functional literacy skills. The research approach used is the Research & Development (R & D) model. The draft functional literacy competency measurement tool has been validated by teachers, experts and practitioners. This instrument has been discussed in FGDs with teachers from 5 (five) junior high schools in Yogyakarta, The FGD resulted in an agreement on the types of functional literacy consisting of 15 types, namely: literary, digital, document, numerical, environmental, health, tourism, transportation, road safety, language politeness, disaster mitigation, financial, cultural, visual, and social literacy. Product testing was needed as further product development to achieve empirical validity. The number of items was 60 items. The product trial in DIY involved a total of 246 students in grades VII and VIII. The results of the trial analysis with the QUEST program resulted in a probability value at the 0.50 level with an item-based reliability index of 0.98. Mean INFIT MNSQ showed a result of 1.00 with SD. 04, which means the item fits the Rasch model. Items that qualified for the appropriate threshold range (± 2) were 51 items or 85%. The items that were outside the ±2 range were 9 items, meaning that the eliminated items were 15%. Students' functional literacy skills in general mostly did not meet the minimum requirement of 75. Students who scored ≥ 75 were 94 students (38.2%). Meanwhile, 61.8% of students did not meet the standardKeywords: instrument, literacy, functional literacy